Group 4 permethylindenyl constrained geometry complexes for ethylene polymerisation catalysis - Williams, T; Buffet, J; Turner, Z; O'Hare, D (Royal Society of Chemistry, 2018)
The synthesis and characterisation of six permethylindenyl constrained geometry complexes is reported. Slurry phase ethylene polymerisation studies demonstrate that activities increase with increasing electron donating character of the amido fragment.